Graphene/PSMA composite for gas sensing application - Hanis Camelia Muhar; Noor Syazwana Sahar; Fauzan Khairi Che Harun; Nurul Ashikin Abdul-Kadir (Institute of Advanced Engineering and Science, 2020)
This paper presents the fabrication of conducting polymer sensor which comprise of graphene-poly styrene-co-maleic acid (PSMA) composite that responds to volatile organic compound (VOC) via a change in the electrical resistance of the sensors. Five sensors composed of different material ratio were fabricated to find out the most prominent weight percentage ratio (wt %) for optimum sensor response. Those materials were deposited onto silver electrode using drop-casting method. NI Card PCIE-6323 measures the voltage obtained from the sensor circuit and the resistance of the gas sensor monitored using LabVIEW instrument. It was observed from the experiments that combination of 60% graphene and 40% PSMA gives the highest sensor response.